1970
DOI: 10.2466/pr0.1970.27.3.967
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Hostility Guilt and Several Measures of Hostility

Abstract: Scores on Mosher's forced-choice Hostility Guilt Scale for females were related to a projective and an objective measure of hostility. The projective measure was the extent to which 70 female undergraduates used the hostile alternative in making up sentences to a list of homonyms with hostile and neutral meanings. The objective measure was the Buss-Durkee Hostility Inventory. Hostility guilt correlated negatively and significantly with the projective measure and with the following Buss-Durkee scales: Assault, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

1974
1974
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 2 publications
0
7
1
Order By: Relevance
“…This study is the first report of a direct behavioral validation of this particular subscale of the MIST. Schill and Schneider (1970) have reported no significant correlations between the Buss-Durkee Hostihty Guilt Scale and the Mosher Scale used m the present study. However, this lack of correlation is not surprismg when it is remembered that the Buss-Durkee Scale is supposedly a measure of guilt as a feeling state whereas Mosher argues that his aggressionguilt scale is a measure of the disposition to inhibit (or not to inhibit) aggression in the face of provocations.…”
Section: Test Measurescontrasting
confidence: 61%
“…This study is the first report of a direct behavioral validation of this particular subscale of the MIST. Schill and Schneider (1970) have reported no significant correlations between the Buss-Durkee Hostihty Guilt Scale and the Mosher Scale used m the present study. However, this lack of correlation is not surprismg when it is remembered that the Buss-Durkee Scale is supposedly a measure of guilt as a feeling state whereas Mosher argues that his aggressionguilt scale is a measure of the disposition to inhibit (or not to inhibit) aggression in the face of provocations.…”
Section: Test Measurescontrasting
confidence: 61%
“…The hostility-guilt subscale reflects guilty affect and cognition about aggressive behaviour. It is a well-validated measure of 'a disposition to inhibit aggression when faced with provocations' (Mosher, 1979;Schill & Schneider, 1970). The guilty conscience subscale mainly reflects self-blame and self-punitiveness, and to a small extent moral standards.…”
Section: Guilt and Expressed Emotionmentioning
confidence: 99%
“…Several studies using the Mosher Guilt Inventories and other guilt scales have shown that proneness to guilt inhibits aggression towards others (Abramson et al, 1977;Caprara etal., 1992;Persons, 1970;Schill & Schneider, 1970;Tangney etal., 1992a). In our study, we have shown that this also applies to relatives' attitudes towards a psychotic patient.…”
Section: Hostility -Guilt In Relation To Criticism and Hostilitymentioning
confidence: 99%
“…A considerable body of research indicates that women engage in aggression less frequently and less extremely than do men. Furthermore, women experience more anxiety about expressing aggression than do men (Brock and Buss 1964;Schill and Schneider 1970;Schill 1972). It seems likely that women, in relating aggressive episodes, would be more likely to see aggression as personally and socially anomic and to anticipate condemnation from the audience.…”
Section: Introductionmentioning
confidence: 99%